Cardiovascular Events and Stimulants for ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers from Vanderbilt University, TN; Kaiser Permanente, California; and other centers conducted a retrospective cohort study of serious cardiovascular events in 1,200,438 children and young adults, ages 2 to 24 years (mean 11.1 years), with ADHD.